Single-Myb-histone proteins from Arabidopsis thaliana: a quantitative study of telomere-binding specificity and kinetics - Hofr, Ctirad; Sultesová, Pavla; Zimmermann, Michal; Mozgová, Iva; Procházková Schrumpfová, Petra; Wimmerová, Michaela; Fajkus, Jirí (The Biochemical journal, 2009)
Proteins that bind telomeric DNA modulate the structure of chromosome ends and control telomere function and maintenance. It has been shown that AtTRB (Arabidopsis thaliana telomere-repeat-binding factor) proteins from the SMH (single-Myb-histone) family selectively bind double-stranded telomeric DNA and interact with the telomeric protein AtPOT1b (A. thaliana protection of telomeres 1b), which is involved in telomere capping. In the present study, we performed the first quantitative DNA-binding study of this plant-specific family of proteins. Interactions of full-length proteins AtTRB1 and AtTRB3 with telomeric DNA were analysed by electrophoretic mobility-shift assay, fluorescence anisotropy and surface plasmon resonance to reveal their binding stoichiometry and kinetics. Kinetic analyses at different salt conditions enabled us to estimate the electrostatic component of binding and explain different affinities of the two proteins to telomeric DNA. On the basis of available data, a putative model explaining the binding stoichiometry and the protein arrangement on telomeric DNA is presented.
Keywords: kinetika; Protein Binding; Electrophoretic Mobility Shift Assay; Arabidopsis Proteins; proteiny huseníčku; Surface Plasmon Resonance; Models, Biological; histony; retardační test; Histones; fluorescenční polarizace; vazba proteinů; Kinetics; biologické modely; Telomere; telomery; povrchová plasmonová rezonance; Fluorescence Polarization; Arabidopsis